1994
DOI: 10.1007/bf01826181
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cardiovascular reflexes in pregnancy. A longitudinal study

Abstract: Cardiovascular reflexes were studied in 22 healthy women before they were pregnant, once during each pregnancy trimester and after delivery to evaluate the effect of pregnancy on autonomic control of haemodynamics. The Valsalva manoeuvre, the deep breathing test, the orthostatic test and the isometric handgrip test were used to assess changes in autonomic nervous function. We found that pregnancy altered the heart rate response in the Valsalva manoeuvre, the deep breathing test and the orthostatic tests. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 17 publications
5
49
1
4
Order By: Relevance
“…Moreover, in orthostatic position heart rate and diastolic blood pressure variability of healthy pregnants were lower compared to non-pregnant women, confirming the possibility of changes in the baroreflex control and increased maternal blood volume to be involved. 20 Nevertheless, in our study, normal pregnant and pre-eclamptic women showed significantly increased heart rate with standing, also if the increase was lower compared to non-pregnant women (9.8% and 13.8%, vs 21.9%, respectively).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Moreover, in orthostatic position heart rate and diastolic blood pressure variability of healthy pregnants were lower compared to non-pregnant women, confirming the possibility of changes in the baroreflex control and increased maternal blood volume to be involved. 20 Nevertheless, in our study, normal pregnant and pre-eclamptic women showed significantly increased heart rate with standing, also if the increase was lower compared to non-pregnant women (9.8% and 13.8%, vs 21.9%, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…[20][21][22][23] On the contrary, many animal studies 24,25 showed pregnancy to be associated with an impaired baroreflex sensitivity, and an attenuated ability to increase sympathetic outflow above baseline levels during a hypotensive challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[17] In our study of HR response to deep breathing, the ratio of maximum-to-minimum RR-interval during respiratory cycles, that is, the E/I ratio of RR intervals, was found to be significantly less in the second trimester compared to controls. In accordance with our results, many studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed HR response to deep breathing expressed as deep breathing difference (DBD), a measure of cardiac parasympathetic function was observed to be significantly lower in pregnant women when compared to control group and generally followed a decreasing trend with increase in gestation. [4] This finding was in conformity with observation of Ekholm et al who suggested a multifactorial basis for it.…”
Section: Discussionsupporting
confidence: 88%
“…[19] A diminished parasympathetic input to the heart during pregnancy has been attributed to, reduced baroreceptor sensitivity, impaired vagal afferents to brain and altered efferent signals to the heart. [20] A reduction in oscillation of the right atrial distension arising from diminished pulsatility of venous return from the growing uterus has been described in pregnant subjects, which may account for the lowering of DBD in pregnancy. [4] …”
Section: Discussionmentioning
confidence: 99%
“…It is known that maternal hemodynamic disturbances play an important role in the development of several diseases in pregnancy, which was demonstrated by Jia et al [12] using noninvasive assessment of maternal cardiovascular parameters. In the presence of maternal heart disease, the main issue is to assess the consequences of disease progression due to the adaptation of the cardiovascular system to pregnancy: plasma catecholamine concentrations and adrenergic receptor sensitivity increase [13]. …”
Section: Discussionmentioning
confidence: 99%